Patrimônio arquitetônico de Santarém: memórias e histórias dos sujeitos locais - GONÇALVES, Karina Barros (Universidade Federal do Oeste do Pará, 2023)
The present dissertation is about the study of culture and the rescue of the memories of the elderly and the social history of the environment, and seeks to answer the scientific question that will guide the research, namely, the downtown neighborhood of the city of Santarém has been valued and preserved in its architectural structure according to the memorial accounts of the elderly people who live in this region? With this purpose in mind, we intend to achieve our objectives, which were to investigate scenarios of architectural heritage in the memory and history of social subjects who experienced the historical constructions of the municipality of Santarém; register the memorial narrations of the elderly and bring to the scenario of Amazonian cultural studies their presences that were as if deadened in everyday life and, mainly, to value such narrations of the people involved in the research, highlighting the expressiveness of the elders about the conflicting action between preserving and the urban transform. In our methodological procedure, we chose to use a qualitative approach to research with the record of oral history from and through an interview script for recording reports and collecting information in the field. The writing of the dissertation was focused on a conception of study about culture and the use of memorial narratives of the elderly as tools for preserving not only their memories but also the culture of the Amazonian people who live in the western region of Pará, on the banks of the Tapajós River, and as an answer to the scientific question that we propose to answer in our research.